Możliwość zastosowania gier komputerowych w treningu mentalnym = The applicability of computer games in mental training - Koperska, Natalia (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The computer games industry is growing rapidly and is attracting more and more fans. It is increasingly difficult to find a young or middle-agedperson who would not enjoy this type of entertainment. This also applies to athletes. For this reason, computer games and their impact on their users are becoming an object of interest for researchers. The aim of this literature review was to describe the latest research results concerning the applicability of computer games in mental training.
Keywords: percepcja; uwaga; podejmowanie decyzji; umiejętności interpersonalne; komunikacja; perception; attention; decision making; interpersonal skills; communication